Functional roles of two novel P450 genes in the adaptability of Conogethes punctiferalis to three commonly used pesticides - Yuan, Xingxing; Li, Han; Guo, Xianru; Jiang, He; Zhang, Qi; Zhang, Lijuan; Wang, Gaoping; Li, Weizheng; Zhao, Man (Frontiers in Physiology, 2023)
Introduction: Insect cytochrome P450 (CYP450) genes play important roles in the detoxification and metabolism of xenobiotics, such as plant allelochemicals, mycotoxins and pesticides. The polyphagous Conogethes punctiferalis is a serious economic pest of fruit trees and agricultural crops, and it shows high adaptability to different living environments. Methods: The two novel P450 genes CYP6CV1 and CYP6AB51 were identified and characterized. Quantitative real-time PCR (qRT-PCR) technology was used to study the expression patterns of the two target genes in different larval developmental stages and tissues of C. punctiferalis. Furthermore, RNA interference (RNAi) technology was used to study the potential functions of the two P450 genes by treating RNAi-silenced larvae with three commonly used pesticides. Results: The CYP6CV1 and CYP6AB51 genes were expressed throughout various C. punctiferalis larval stages and in different tissues. Their expression levels increased along with larval development, and expression levels of the two target genes in the midgut were significantly higher than in other tissues. The toxicity bioassay results showed that the LC50 values of chlorantraniliprole, emamectin benzoate and lambda-cyhalothrin on C. punctiferalis larvae were 0.2028 μg/g, 0.0683 μg/g and 0.6110 mg/L, respectively. After treating with different concentrations of chlorantraniliprole, emamectin benzoate and lambda-cyhalothrin (LC10, LC30, LC50), independently, the relative expressions of the two genes CYP6CV1 and CYP6AB51 were significantly induced. After the dsRNA injection, the expression profiles of the two CYP genes were reduced 72.91% and 70.94%, respectively, and the mortality rates of the larvae significantly increased when treated with the three insecticides independently at LC10 values. Discussion: In the summary, after interfering with the CYP6CV1 and CYP6AB51 in C. punctiferalis, respectively, the sensitivity of C. punctiferalis to chlorantraniliprole, emamectin benzoate and lambda-cyhalothrin was significantly increased, indicating that the two CYP6 genes were responsible for the adaptability of C. punctiferalis to the three chemical insecticides in C. punctiferalis. The results from this study demonstrated that CYP6CV1 and CYP6AB51 in C. punctiferalis play crucial roles in the detoxification of chlorantraniliprole, emamectin benzoate and lambda-cyhalothrin.